Impact of fracture reduction quality on clinical outcomes in hip arthroplasty for intertrochanteric fractures based on a novel radiographic evaluation system: a retrospective study - Zhang, Binquan; Huo, Jia; Li, Huijie (Frontiers in Medicine, 2025)
BackgroundThe impact of fracture reduction quality on clinical outcomes in hip arthroplasty for intertrochanteric fractures remains insufficiently characterized. This study aimed to establish a standardized postoperative radiographic evaluation system for reduction quality and assess its correlation with postoperative function and complications.MethodsA retrospective cohort study included 237 patients undergoing hip arthroplasty for intertrochanteric fractures (2012–2024). Reduction quality was classified as optimal, acceptable, or poor based on four criteria: (1) greater trochanter alignment, (2) lesser trochanter reduction, (3) femoral stem stability, and (4) postoperative femoral anteversion (optimal: 13 ± 3°; acceptable: 6–10° or 16–20°; poor: <6° or >20°). Outcomes included Harris Hip Scores, Engh's scores, delayed healing, and complications. Statistical analyses were adjusted for AO/OTA fracture classification.ResultsOptimal reduction (Grade A, n = 107) correlated with superior Harris Hip Scores (92.57 ± 4.27 vs. 82.46 ± 7.05, P < 0.001), lower delayed healing (3.74% vs. 14.29%, P = 0.031), and reduced abductor weakness (1.87% vs. 14.29%, P = 0.014). Acceptable reductions (Grade B, n = 74) showed intermediate outcomes. Poor reductions (Grade C, n = 56) exhibited the highest complication rates. Engh's scores were significantly higher in Grade A (97.20% vs. 73.21%, P = 0.002). Dislocation and heterotopic ossification rates did not differ significantly (P > 0.05).ConclusionThis study introduced and validated a standardized radiographic evaluation system to assess reduction quality in arthroplasty for intertrochanteric fractures, emphasizing the prognostic importance of anatomic trochanteric alignment and cortical continuity. High-quality reduction is critical for optimizing functional recovery and minimizing complications in arthroplasty for intertrochanteric fractures. Future research should explore long-term outcomes and advanced fixation techniques to enhance reduction precision.